Lived experiences of student nurses caring for intellectually disabled people in a public psychiatric institution - Annie Temane; Lizzie Simelane; Marie Poggenpoel; C.P.H. Myburgh (AOSIS, 2016)
Background: Caring for intellectually disabled people can be demanding for student nurses who are novices in the nursing profession. To ensure that quality nursing care is provided, student nurses should have an understanding of and a positive attitude towards intellectually disabled people. Nursing intellectually disabled people can be a challenge for the student nurses. Therefore, student nurses need to be able to deal with challenges of caring for intellectually disabled people. Objective: This article aims to explore and describe experiences of student nurses caring for intellectually disabled people in a public psychiatric institution. Design and method: A qualitative, exploratory, descriptive and contextual research design was used. Data were collected through individual in-depth phenomenological interviews, naïve sketches and field notes. Thematic analysis was utilised to analyse the collected data. Results were contextualised within the literature and measures to ensure trustworthiness were adhered to. Ethical principals were also applied throughout the research process. Results: Five themes emerged from the data. Student nurses experienced a profoundly unsettling impact on their whole being when caring for intellectually disabled people; they developed a sense of compassion and a new way of looking at life, and experienced a need for certain physical, mental and spiritual needs to be met. Conclusion: From the results, it is evident that student nurses were challenged in caring for intellectually disabled people. However, they developed a sense of awareness that intellectually disabled people have a need to be cared for like any other person. Keywords: experiences, student nurses, caring, intellectually disabled people, public psychiatric institution